KEBIJAKAN PENGEMBANGAN INFRASTRUKTUR TRANSPORTASI LAUT PADA DINAS PERHUBUNGAN KABUPATEN MUNA BARAT - Sartono Sartono (Journal Publicuho, 2019)
This study aims to determine the policies carried out by the transportation agency in an effort to develop marine transportation infrastructure and the benefit that can be obtained in the development of the marine transportation infrastructure.The informant in this study consisted of ahead of the department transportation districts Muna Barat, secretary department transportation districts Muna Barat, and head of development and safety department transportation districts Muna Barat.The results of this study indicate that policy department transportation districtsMuna Barat in development infrastructure water transportation seen from three policies. First, infrastructure investment is considered good seen from the collaboration done with several parties which have to invest several ships that have been operated in several ports which exist in Muna Barat. Second, development infrastructure port assessed already enough good seen from development docks and port which exists in islands small in region districts Muna Barat. Third, expansion capacity port assessed already good seen from additions long from port people Latawe and port people Pajala and additions large at the port Tondasi. Benefit development infrastructure port covers economic growth, job creation, and development of economic national and regional. If seen from the fact that is there can be it is said that as is development port or infrastructure water transportation then very have a positive impact on economic growth, job creation, and development economic national and regional because the port is an asset regional and country very important in support smooth turnaround the wheel economic remembering Indonesia is archipelago state.